The Good German - Soderbergh, Steven, 1963-; Cosgrove, Ben; Jacobs, Gregory; Attanasio, Paul, 1959-; Clooney, George; Blanchett, Cate, 1969-; Kanon, Joseph; Warner Bros. Pictures (1969- ); Virtual Studios; Section Eight Ltd.; Copyright Collection (Library of Congress) (United States : Warner Bros. Pictures, 2006)
Takes place in the ruins of post-WWII Berlin, where U.S. Army war correspondent Jake Geismar becomes involved with Lena Brandt, a former lover whose missing husband is the object of a manhunt led by both the American and Russian armies. Jake tries to uncover the secrets Lena may be hiding in her desperation to get herself and her husband out of Berlin. Tully is an American soldier working in the U.S. Army motor pool who is assigned to drive Jake around Berlin. Tully has black market connections that may be Lena's way out. But he could lead them all into even darker territory.
Copyright: Warner Brothers Entertainment, Inc. & Virtual Studios, LLC. PREV: Novel by Joseph Kanon & screenplay by Paul Attanasio, archival footage, sound recordings, film footage, musical compositions preexisting. DCR 2006; PUB 15Dec06; REG 16Mar07; PA1-366-628.
Summary adapted from FirstSearch, OCLC 86111774, viewed Dec. 4, 2007.
Based on the novel by Joseph Kanon.
Not viewed.
Sources used: Copyright data sheet; Copyright database; Variety Web site, review posted Nov. 30, 2006, viewed Dec. 4, 2007; Internet movie database, viewed Dec. 4, 2007; FirstSearch, OCLC 86111774, viewed Dec. 4, 2007.
Executive producers, Benjamin Waisbren, Frederic W. Brost ; camera, Peter Andrews ; editing, Mary Ann Bernard ; music, Thomas Newman.
Keywords: War correspondents -- Germany -- Berlin -- Drama; Missing persons -- Investigation -- Germany -- Berlin -- Drama; Triangles (Interpersonal relations) -- Germany -- Berlin -- Drama; Thriller -- Feature; Adaptation -- Feature